If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x+20-7x=2(5x+10)
We move all terms to the left:
-3x+20-7x-(2(5x+10))=0
We add all the numbers together, and all the variables
-10x-(2(5x+10))+20=0
We calculate terms in parentheses: -(2(5x+10)), so:We get rid of parentheses
2(5x+10)
We multiply parentheses
10x+20
Back to the equation:
-(10x+20)
-10x-10x-20+20=0
We add all the numbers together, and all the variables
-20x=0
x=0/-20
x=0
| 4m^2+3=403 | | -6(x+4)=2x-16 | | 44-5x=25 | | -2/5(9v+3)=-7 | | -15-14x=13-15x | | 12+4x=4x+26 | | 6(7-6x)=42 | | 2.5x-7=4x+2 | | 3-5x=3x-5 | | -6(x-17)=36 | | -1/2x-(1/2+4)+12=17x-6(3x+5/6) | | 13+7(-3x+-1)=-63 | | 3.1(t+1.3)=8.37 | | -10x-196=76+7x | | 14=a-3 | | -11+x=7-8(-x+1) | | 3x+20=-2x+15 | | 4/3p=1/5 | | 3=12-d | | 8x-7=2x5 | | y/2+4=12 | | x/2=6=1 | | -3-4x=-21 | | 3x-4=11,x=5 | | x2/3+6=30 | | 7/10=3/x-1 | | 5(t+2)-2=6t-9 | | 13x-3=5x+2 | | 3^3*x=23 | | 2(3x+4)-3x=3x+8 | | (x⅔)+6=30 | | (6x-15)+(2x+18)+(2x−13)=180 |